Why Legal Reform is Insufficient to Ensure Sexual Equality. Issue 1 (September 2017) - Misra, Geetanjali; Ferdous, Nafisa
Abstract The history of decriminalization and other sexual rights struggles as they intersect with legal reform was highlighted in the 2016 AWID Forum. This article takes three case studies from India spanning the movement to decriminalize homosexuality, the violence against women movement and the sex workers rights movement to explore the relationship between cultural change and legal reform.